2018
DOI: 10.20360/langandlit29408
|View full text |Cite
|
Sign up to set email alerts
|

Raising Awareness and Addressing Elder Abuse in the LGBT Community: An Intergenerational Arts Project

Abstract: This paper reports on a collaborative digital arts project conducted with LGBT youth and seniors in Vancouver, British Columbia, Canada, funded by the B.C. Council to Reduce Elder Abuse and conducted by faculty members and a doctoral student from Simon Fraser University. In the project, youth and seniors worked together to produce the first Canadian materials on LGBT elder abuse-three digital videos and five informational posters. We report on the methods used to produce and disseminate the materials, and as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…While there is limited research about digital storytelling to prevent elder abuse, it has been used as a methodology for intergenerational exchange (Hewson et al, 2015) and indigenous Elders' witnessing and healing (Adelson and Olding, 2013). Further, research in Canada has shown the effectiveness of digital storytelling in raising awareness of elder abuse in LGBT communities (Robson et al, 2018), and recent Australian research has used digital and visual storytelling to research intergenerational needs in age-friendly communities (Cook, 2019). The OPERA Project builds on this research to use co-designed digital storytelling both as a research methodology to gain evidence about older people's experiences of ageing and ageism, and as a community practice to centre older people's experiences and voices in the prevention of age-related discrimination.…”
Section: Methodsmentioning
confidence: 99%
“…While there is limited research about digital storytelling to prevent elder abuse, it has been used as a methodology for intergenerational exchange (Hewson et al, 2015) and indigenous Elders' witnessing and healing (Adelson and Olding, 2013). Further, research in Canada has shown the effectiveness of digital storytelling in raising awareness of elder abuse in LGBT communities (Robson et al, 2018), and recent Australian research has used digital and visual storytelling to research intergenerational needs in age-friendly communities (Cook, 2019). The OPERA Project builds on this research to use co-designed digital storytelling both as a research methodology to gain evidence about older people's experiences of ageing and ageism, and as a community practice to centre older people's experiences and voices in the prevention of age-related discrimination.…”
Section: Methodsmentioning
confidence: 99%
“…The abuse of older people is generally under-researched [67] especially in relation to those from minority groups [68]. There is very little research in relation to older LGBTQ people and abuse [69][70][71][72][73][74]. Although there is a growing body of research on LGBTQ intimate partner violence [62,63,[75][76][77][78] this primarily focuses on younger people, with, little research involving older LGBTQ people.…”
Section: Neglect and Acts Of Omission Includingmentioning
confidence: 99%
“…Elder abuse faced by 2SLGBTQI older adults remains an understudied area, while elder abuse prevention efforts have begun to recognize the need to better serve and address the situations of 2SLGBTQI communities. Further research is needed to build on existing knowledge and resources (e.g., Gutman et al, 2020; Pang & Rideout, 2022; Robson et al, 2018), including in Canada, to increase understanding of 2SLGBTQI older adults’ situations and needs, and to identify prevention and support strategies. In collaboration with Elder Abuse Prevention Ontario, in 2022, we held a community conversation event focused on elder abuse and financial abuse in 2SLGBTQI communities and published an open-access brief that highlighted existing research, reported back on event findings, and provided resources geared towards 2SLGBTQI older adults (Pang & Rideout, 2022).…”
Section: Increasing Knowledge Of the Mental Health Care Access Needs ...mentioning
confidence: 99%